2012
DOI: 10.1007/s00467-011-2096-2
|View full text |Cite
|
Sign up to set email alerts
|

A mitochondrial DNA deletion presenting with corneal clouding and severe Fanconi syndrome

Abstract: The finding of Fanconi syndrome with disease processes in other, seemingly unrelated, organ systems should raise clinical suspicion for mitochondrial disease. Early assessment of urine organic acids in the etiological work-up of Fanconi syndrome may assist in the identification of respiratory chain disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…Similar reports exist for Kearns-Sayre (KSS) [47][48][49][50] and Leigh syndrome [40]. Several studies have found large mtDNA deletions in mitochondrial DNA to be the underlying cause, ranging from 2.7 to 7.4 kbp deletions [48,[51][52][53][54][55]. Overall, these patients show phenotypic similarities to Pearson and Kearns-Sayre syndromes.…”
Section: Mutationssupporting
confidence: 72%
“…Similar reports exist for Kearns-Sayre (KSS) [47][48][49][50] and Leigh syndrome [40]. Several studies have found large mtDNA deletions in mitochondrial DNA to be the underlying cause, ranging from 2.7 to 7.4 kbp deletions [48,[51][52][53][54][55]. Overall, these patients show phenotypic similarities to Pearson and Kearns-Sayre syndromes.…”
Section: Mutationssupporting
confidence: 72%
“…The most common tubular defect associated with MCs is Toni-Debré-Fanconi syndrome, a rare disorder characterized by impaired tubular reabsorption. Mutations and large mtDNA deletions have been reported in patients with this syndrome (Lee et al 2012), associated with mitochondrial respiratory complex defects and giant atypical mitochondria (Au et al 2007). Kearns–Sayre syndrome, an MC caused by deletions of mtDNA and characterized by isolated involvement of the muscles controlling eyelid movement, may present with renal involvement resembling Barter syndrome (Emma et al 2006).…”
Section: Evidence Of Mitochondrial Injury In Renal Diseasementioning
confidence: 99%
“…[22][23][24] Furthermore, the renal phenotype of HNF1B mutated individuals overlaps with that of patients with renal mitochondrial disorders (i.e., interstitial fibrosis, electrolyte disorders, and rarely, proximal tubular dysfunction). 15,25,26 We therefore hypothesized that (1) HNF-1b may directly control PPARGC1A expression and subsequent mitochondrial biogenesis or function in the postembryonic kidney, thus shifting the paradigm of the HNF1B-related nephropathy in adulthood from a developmental nephropathy to a mitochondrial disorder; and (2) transient HNF-1b inhibition may control the mitochondrial dysfunction observed at the early phases of AKI.…”
mentioning
confidence: 99%